Silica-coated magnetic palladium nanocatalyst for Suzuki-Miyaura cross-coupling - Md. Lutfor Rahman; Mohd Sani Sarjadi; Mohammed Salim Akhter; John J. Hannan; Shaheen M. Sarkar (Elsevier Science, 2022)
A silica-coated magnetically separable Schiff-base palladium nanocatalyst was developed. Amorphous silica was used to encapsulate the magnetic Fe3O4 and an organic amine functionality was added to the silica surface. The amino group was treated with 1, 10- phenanthroline-2,9-dicarboxaldehyde to produce a Schiff-base, which was then treated with palladium to produce the silica coated magnetic Schiff-base palladium nanocatalyst. The palladium nanocatalyst was fully characterized using several spectroscopic techniques. The HR-SEM image of silica coated Fe3O4 revealed a globular shape with a diameter of 145 nm, along with this the average palladium nanoparticle size was 3.5 ± 0.6 nm. The successful functionalization and the appearances of the palladium species as a magnetic catalyst was confirmed by FT-IR and XRD analysis. The palladium nanocatalyst was successfully applied for the construction of CAC bonds via Suzuki- Miyaura reaction. With a variety of organoboronic acids, the catalyst displayed great performance for electron-poor and electron-rich aryl halides, resulting in excellent yields of the corresponding cross-coupling products. The magnetic catalyst was retrieved from the reaction vial using an external strong magnet, and it was reused seven times without a significant drop in the production of the corresponding biaryl product.